Bioinspired Molecular Factories with Architecture and In Vivo Functionalities as Cell Mimics. Issue 4 (9th January 2020) - Einfalt, Tomaž; Garni, Martina; Witzigmann, Dominik; Sieber, Sandro; Baltisberger, Niklaus; Huwyler, Jörg; Meier, Wolfgang; Palivan, Cornelia G.
Abstract: Despite huge need in the medical domain and significant development efforts, artificial cells to date have limited composition and functionality. Although some artificial cells have proven successful for producing therapeutics or performing in vitro specific reactions, they have not been investigated in vivo to determine whether they preserve their architecture and functionality while avoiding toxicity. Here, these limitations are overcome and customizable cell mimic is achieved—molecular factories (MFs)—by supplementing giant plasma membrane vesicles derived from donor cells with nanometer‐sized artificial organelles (AOs). MFs inherit the donor cell's natural cytoplasm and membrane, while the AOs house reactive components and provide cell‐like architecture and functionality. It is demonstrated that reactions inside AOs take place in a close‐to‐nature environment due to the unprecedented level of complexity in the composition of the MFs. It is further demonstrated that in a zebrafish vertebrate animal model, these cell mimics show no apparent toxicity and retain their integrity and function. The unique advantages of highly varied composition, multicompartmentalized architecture, and preserved functionality in vivo open new biological avenues ranging from the study of biorelevant processes in robust cell‐like environments to the production of specific bioactive compounds. Abstract : Strategy for creating bioinspired molecular factories. Prior formed artificial organelles are integrated together with various cargoes (small molecular weight molecules, biomacromolecules, and combinations of thereof) into giant plasma membrane vesicles generated by donor cells. Transfer of material from the donor cell cytoplasm and membrane is achieved during vesicle formation, resulting in compartment‐in‐compartment architecture of the molecular machinery.